2018
DOI: 10.1038/s41467-018-05568-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confined peptide assemblies with tunable visible to near-infrared spectral range

Abstract: Quantum confined materials have been extensively studied for photoluminescent applications. Due to intrinsic limitations of low biocompatibility and challenging modulation, the utilization of conventional inorganic quantum confined photoluminescent materials in bio-imaging and bio-machine interface faces critical restrictions. Here, we present aromatic cyclo-dipeptides that dimerize into quantum dots, which serve as building blocks to further self-assemble into quantum confined supramolecular structures with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
127
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 62 publications
10
127
1
Order By: Relevance
“…Fourier‐transform infrared spectroscopy (FTIR) analysis indicated that after Zn(II) coordination, the NH stretching vibration peaks of the cyclo‐HH became narrower and sharper, indicating that less hydrogen bonds were formed and many NH moieties remained free. In addition, the insert backbone CC stretching vibration peaks became relatively stronger, indirectly confirming that the active nitrogen atoms extensively participated in complexation with Zn(II) and the coordination distinctly hindered the IR absorption of the relevant chemical bonds . This confirmed that the active nitrogen atoms extensively participated in complexation with Zn(II) (Figure S8, Supporting Information), as we previously demonstrated for cyclo‐WW + Zn(II) . ]…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Fourier‐transform infrared spectroscopy (FTIR) analysis indicated that after Zn(II) coordination, the NH stretching vibration peaks of the cyclo‐HH became narrower and sharper, indicating that less hydrogen bonds were formed and many NH moieties remained free. In addition, the insert backbone CC stretching vibration peaks became relatively stronger, indirectly confirming that the active nitrogen atoms extensively participated in complexation with Zn(II) and the coordination distinctly hindered the IR absorption of the relevant chemical bonds . This confirmed that the active nitrogen atoms extensively participated in complexation with Zn(II) (Figure S8, Supporting Information), as we previously demonstrated for cyclo‐WW + Zn(II) . ]…”
Section: Resultssupporting
confidence: 75%
“…Simultaneously, the photoluminescence efficiency was improved, with an enhanced QY of 15% for cyclo‐HH + Zn(II) (Table ). The emission of the cyclo‐HY solution was also enhanced to some extent in the presence of Zn(II), with the λ Em detected at 490 nm (Ex: 380 nm) (Figure S5, Supporting Information), τ of 4.79 ns and a QY of 9% (Table ), similarly to cyclo‐WW, as we have previously published . In contrast, the other dipeptides did not show any noticeable changes in the presence of Zn(II) (Figures S6 and S7, Supporting Information).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations